Antimicrobial Resistance Surveillance in Post-Soviet Countries: A Systematic Review - Dariga Zhazykhbayeva; Dinagul Bayesheva; Zhanar Kosherova; Yuliya Semenova (Antibiotics)
Background: Antimicrobial resistance (AMR) is a global health threat. AMR surveillance is crucial for understanding and controlling the spread of AMR. Surveillance systems can inform clinicians, guide health policymakers, and support effective AMR interventions. AMR surveillance data from former Soviet region countries are often limited, resulting in gaps in up-to-date knowledge. Methods: This systematic review was registered under the PROSPERO protocol CRD42024537799 and followed the PRISMA guidelines. Data from five databases (PubMed, MEDLINE, Embase, CINAHL, and CyberLeninka) and official sources were searched according to the inclusion criteria. Results: In total, 30 publications describing AMR surveillance and National Action Plans (NAPs) were included. Among the 15 countries, 14 (93.3%) have either developed a NAP or are in the process of implementing one; and 7 (46.7%) countries have a standardized AMR surveillance system. Almost all countries have reference laboratory centers, but nine (60%) countries have established standard testing methods in all sites. Only three (20%) countries have fully implemented quality assessment. There is an increasing tendency to involve and report AMR data to international networks, and countries will strengthen their AMR systems by adhering to international standards. The subgroup analysis revealed that Central and Western Asian countries are less developed in terms of AMR surveillance, which may encourage proactive engagement in AMR governance in these regions. Conclusions: This review is crucial for understanding the current efforts and improving AMR surveillance in former Soviet countries. The findings are promising and indicate that AMR surveillance is established in all reviewed countries, although at different levels.